Experimenting with purchase history based price discrimination: A comment - Michel Tolksdorf (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
Brokesova, Deck and Peliova [Int. J. Ind. Organ. 37 (2014) 229-237] have shown that comparative static results from two-period behavior-based pricing models hold in laboratory experiments, but they observed significant differences from point predictions. We report findings in conformity with these point predictions throughout a uniform pricing benchmark, a replication of Brokesova, Deck and Peliova's behavior-based pricing treatment and a follow-up experiment. Reference dependence seems to shift participants' second-period pricing behavior upwards. A post hoc analysis shows that considering myopic consumers instead of strategic consumers explains a downward shift of first-period prices and rationalizes the findings of Brokesova, Deck and Peliova. Volatile price levels affect price-based welfare measures such as sellers' profits and customers' total costs. We show that transport costs serve as a robust welfare measure, alleviating the impact of distorted prices. These findings are relevant for the design of experiments and when assessing the efficiency of experimental markets.
Keywords: D43; L13; 330; Behavior-based price discrimination; pricing experiment